Should chloroquine and hydroxychloroquine be used to treat COVID-19? A rapid review - Gbinigie, O; Frie, K (Royal College of General Practitioners, 2020)
Background On the 11 March 2020, the World Health Organization (WHO) declared that COVID-19 was a pandemic. To date, there are no medical treatments for COVID-19 with proven effectiveness. Novel treatments and/or vaccines will take time to be developed and distributed to patients. In light of this, there has been growing interest in the use of existing medications, such as chloroquine (CQ) and hydroxychloroquine (HCQ), as potential treatments of this disease.